2019
DOI: 10.1097/aog.0000000000003286
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacist Provision of Hormonal Contraception in the Oregon Medicaid Population

Abstract: Financial DisclosureDaniel Hartung has received money paid to his institution (grant funding) from NIH, CDC, AHRQ, National MS Society, and AbbVie Pharmaceuticals. He has a consulting contract with MedSavvy. Maria Rodriguez received money paid to her institution from the Laura and John Arnold Foundation and World Health Organization. She was on a medical advisory board for Cooper Surgical and has been a contraceptive implant trainer for Merck. She was also a WRHR Scholar with NICHD funding in the past (which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 9 publications
3
56
3
Order By: Relevance
“…Of the patients who received contraception, 5% had a U.S. MEC Category 3 or 4 medical condition that was not identified during pharmacist screening. This frequency of error is similar to that of clinicians' (5% to 8%) seen in a 2011 study of contraception contraindications [13,14]. A study of telehealth providers found that 7% of appointments were noncompliant with the U.S. MEC [15].…”
Section: Safetysupporting
confidence: 74%
See 1 more Smart Citation
“…Of the patients who received contraception, 5% had a U.S. MEC Category 3 or 4 medical condition that was not identified during pharmacist screening. This frequency of error is similar to that of clinicians' (5% to 8%) seen in a 2011 study of contraception contraindications [13,14]. A study of telehealth providers found that 7% of appointments were noncompliant with the U.S. MEC [15].…”
Section: Safetysupporting
confidence: 74%
“…This grew to 60 claims per month by month seven. Pharmacists prescribed 10% of all transdermal and oral contraception products for Medicaid patients [13]. Data from Oregon and New Mexico reveal that these services are provided in both rural and urban settings [34].…”
Section: Availability and Pharmacist Adoptionmentioning
confidence: 99%
“…26 In the Oregon Medicaid population, from January 2016 to December 2017, 10% of oral and transdermal contraceptive prescriptions were written by a pharmacist. 27 Oregon pharmacists were surveyed at 6 and 12 months postimplementation of the prescribing policy in 2016. 28 Responders included 732 pharmacists, and there was an increase in the distribution of contraception prescription prescribing by ZIP code at 6 (19%) and 12 months (63%) postimplementation.…”
Section: Methodsmentioning
confidence: 99%
“…6 From January 1, 2016, to December 31, 2017, 10% of new prescriptions for oral or transdermal contraceptives in Oregon's Medicaid population were prescribed by pharmacists, with an estimated 51 unintended pregnancies averted. 7,8 Anderson et al identified having a consistent training program as a key aspect of successful implementation of pharmacist-prescribed contraception. 9 Lio et al found, in the Mid-Atlantic division of a grocery store chain, that pharmacists reported low knowledge of and comfort with prescribing contraception and that both significantly increased after a training session, supporting Anderson et al's assertion that education can increase the likelihood of pharmacists offering this service.…”
mentioning
confidence: 99%